2022
DOI: 10.3390/ijerph19031249
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Role of Vitamins in Athletes’ Muscle, Heart and Microbiota

Abstract: Physical activity, combined with adequate nutrition, is considered a protective factor against cardiovascular disease, musculoskeletal disorders, and intestinal dysbiosis. Achieving optimal performance requires a significantly high energy expenditure, which must be correctly supplied to avoid the occurrence of diseases such as muscle injuries, oxidative stress, and heart pathologies, and a decrease in physical performance during competition. Moreover, in sports activities, the replenishment of water, vitamins,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 155 publications
(172 reference statements)
0
42
0
Order By: Relevance
“…A further limitation is the lack of a nutritional table of the subjects. It would have been an important finding as some authors suggest that low levels of magnesium and zinc promote excitotoxicity [ 51 , 52 ]. Another limitation is the lack of a control group that would have helped to strengthen our results.…”
Section: Discussionmentioning
confidence: 99%
“…A further limitation is the lack of a nutritional table of the subjects. It would have been an important finding as some authors suggest that low levels of magnesium and zinc promote excitotoxicity [ 51 , 52 ]. Another limitation is the lack of a control group that would have helped to strengthen our results.…”
Section: Discussionmentioning
confidence: 99%
“…The main objective of our work was to assess whether the athletes studied had serum vitamin D3 deficiency. It should be emphasized that the vitamin D3 status in athletes is an important research problem which, on the one hand, indicates the fundamental role of vitamin D3 supplementation in physical activity (41,42) and, on the other hand, proves the commonly observed vitamin D3 insufficiency/deficiency in athletes (43). We confirmed that in 68% of our study athletes the average baseline 25(OH)D concentration was below 30 ng/mL, which can be classified as insufficiency of vitamin D3.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamins and minerals are the crucial micronutrients needed by the body to regulate multiple functions and the metabolism of the body ( 273 , 274 ). Vitamins and minerals are naturally present in plants.…”
Section: Methodsmentioning
confidence: 99%